2009
DOI: 10.2984/049.063.0408
|View full text |Cite
|
Sign up to set email alerts
|

A Long-Term Perspective on Biodiversity and Marine Resource Exploitation in Fiji's Lau Group

Abstract: I present research investigating biodiversity and human interaction with the local environment through three perspectives on diverse islands in Fiji's Lau Group. First, I generated long-term data on marine diversity and exploitation through zooarchaeological analyses of fauna from sites spanning the region's prehistoric human occupation. The study areas are representative of regional fauna and local geographic variation in island size and structure. Each island also varies in terms of human occupation and degr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 38 publications
3
30
0
Order By: Relevance
“…In sum, the Chelechol ra Orrak data set presents a clear evidence for an increase in humped conch size over time. This finding is noteworthy as previous studies have documented a decline in humped conch size and/or abundance through time in Pacific archaeological sites (Amesbury, 2007;Jones, 2009;Masse et al, 2006).…”
Section: Resultssupporting
confidence: 59%
See 1 more Smart Citation
“…In sum, the Chelechol ra Orrak data set presents a clear evidence for an increase in humped conch size over time. This finding is noteworthy as previous studies have documented a decline in humped conch size and/or abundance through time in Pacific archaeological sites (Amesbury, 2007;Jones, 2009;Masse et al, 2006).…”
Section: Resultssupporting
confidence: 59%
“…In the Pacific Islands, a number of archaeomalacological studies have identified a decline through time in the size and/or abundance of the humped conch (Strombus gibberulus), a species that is often a constituent of archaeological assemblages in this region (Amesbury, 2007;Jones, 2009;Masse et al, 2006). Humped conch is found in relative abundance at the site of Chelechol ra Orrak in Palau in deposits that date from approximately 3000 BP to the present.…”
Section: Introductionmentioning
confidence: 98%
“…Detailed chronologies and site descriptions are published elsewhere (Jones, 2009;Jones et al, 2007;O'Day et al, 2003). Excavations were conducted in 5-10 cm levels, following natural stratigraphy whenever possible.…”
Section: Archaeological Sitesmentioning
confidence: 99%
“…In the center of the study area is Lakeba (55.8 km 2 ), a large volcanic island that has been the focus of archaeological (Best, 1984(Best, , 2002 and ethnoarchaeological research (Jones, 2009). Jones conducted ethnography on Lakeba, but no archaeological data are included herein.…”
Section: Setting and Environmental Contextmentioning
confidence: 99%
See 1 more Smart Citation